The effect of foreign real estate investments on house prices: evidence from emerging economies - Gholipour, Hassan Fereidouni (International Journal of Strategic Property Management, 2013)
In recent years, most emerging economies have experienced large foreign real estate investment (FREI) and an appreciation of house prices. The purpose of this study is to empirically investigate the effects of FREI on house prices by employing a panel VAR model. Using data from 21 emerging economies over the period 2000–2008, our empirical results show that FREI contributes to house price increases. Moreover, the results indicate that the dominant source of house price fluctuations in emerging economies come from the housing market itself.First Publish Online: 3 Apr 2013